ECG Quizz 37 - Answer - Millar, Rob Scott; Chin, Ashley (SA Heart Journal, 2017)
The ECG shows a regular, narrow complex (80ms) tachycardia with a ventricular rate of 180bpm. The rhythm is supraventricular in origin.